William Dorsey and the construction of an African American history archive. (2nd January 2019) - Gonzalez, Aston
ABSTRACT: This article investigates the collecting philosophies and practices of William Henry Dorsey, a nineteenth-century African American collector and archivist in Philadelphia. Over many decades, Dorsey created an archive that documented black professional, artistic, and political accomplishments in order to preserve these histories, influence public perception of African Americans, and enable future research on historical black figures. In doing so, he established and strengthened networks between individuals and associations that shared the goal of celebrating and preserving black history. This article focuses on how Dorsey's archive enabled forms of sociability among the many individuals and groups that used the materials in Dorsey's collection. In focusing on the role that Dorsey played in collating, editing, and disseminating information about black achievements and contributions to world history, this article argues that Dorsey preserved – and therefore helped create – black histories that could be remembered, studied, and shared to refute the illusion of white supremacy.